IMPROVISATION OF MESH NETWORK WITH WIDEBAND CODE DIVISION MULTIPLE ACCESS - Sivaganesan, D. (IRO Journal on Sustainable Wireless Systems, 2019)
Mesh Networks are employed in various applications despite issues relevant to interference and network capacity. These networks also impose delay in routing and reconfiguration. Traditionally, TDMA and FDMA techniques have been used in these networks. This paper proposes wideband code division multiple access (WCDMA) technique for enabling maximum power transfer, low energy consumption, interference free and plugand-play feature enabling easy implementation of the technology. The spatial configuration and node count bounds are stated ensuring continuous satisfaction of quality of service by the communication link. Additionally, dynamic parallel orthogonal transmission and turbo coding schemes are used in combination to improve the efficiency of the network even for large hop counts.
Keywords: Mesh Network; WCDMA; wireless communication; energy efficiency; turbo coding